Saving Private Ryan - Spielberg, Steven, 1946-; Hanks, Tom; Burns, Edward, 1968-; Damon, Matt (Hollywood, Calif. : Paramount Home Entertainment, 2010)
After the D-Day invasion, a squad of American soldiers led by Captain John Miller embarks on a dangerous special mission to penetrate enemy lines and find Private James Ryan, whose three brothers have been killed in combat.
Originally released as a motion picture in 1998.
Features: exclusive message from Steven Spielberg; Saving Private Ryan : "Into the breach"; 2 theatrical trailers; production notes; cast and filmmakers' bios.
Tom Hanks, Edward Burns, Matt Damon, Tom Sizemore.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
Closed-captioned.
Keywords: World War, 1939-1945 -- Search and rescue operations -- Drama; World War, 1939-1945 -- Campaigns -- France -- Normandy -- Drama; World War, 1939-1945 -- Drama; Soldiers -- Drama; Video recordings for the hearing impaired; Fiction films; Feature films; War films